EVALUATION OF DEVELOPMENT LEVEL OF INTEGRATED NON-COMMUNICABLE DISEASES GUIDANCE POST IN MOJOGENENG VILLAGE, JATIREJO HEALTH CENTER, MOJOKERTO REGENCY - Luluk Widarti; Suprianto Suprianto (Journal of Vocational Nursing)
Introduction: PTM is one of the most common causes of death in Indonesia. Based on a preliminary study of data from the Jatirejo Public Health Center in 2018, 2743 families with hypertension were found while those receiving routine treatment were 884 families. In Mojogeneng village, 163 families suffer from hypertension, but only 64 families receive regular treatment. Based on these problems, it can be said that the implementation of the PTM Posbindu in Mojogeneng Village has not run optimally, therefore it is necessary to carry out an evaluation that aims to see the level of development of the PTM Posbindu through 12 indicators according to the UKBM technical guidelines.